Effects of Coronary Artery Bypass Grafting on Cellular Immunity with or without Cardiopulmonary Bypass: Changes in Lymphocytes Subsets - (:unkn) unknown (My University, 2002)
Cell-mediated immunity responses decrease after all kinds of surgical procedures. Either anesthesia or surgical trauma plays an important role in this effect. Identification of functional lymphocyte subsets, by using appropriate monoclonal antibodies and analysis of flow cytometry data, appears to provide an accurate measurement of cellular immune competence. We found a significant decrease in the total number of T helper/inducer cells (p<0.035), B cells (p<0.043) and natural killer cells (NK) (p<0.018) but in contrast, increase in NK cell activity (p<0.012) in the peripheral arterial blood of ten patients undergoing coronary artery bypass grafting with cardiopulmonary bypass (group 1) immediately after surgery and postoperative day 1 (POD1). On the other hand, there was no significant change of these parameters occurred in the peripheral arterial blood of ten patients (group 2) who were undergoing coronary artery bypass grafting without cardiopulmonary bypass. Therefore, we conclude that coronary artery bypass grafting (CABG) with cardiopulmonary bypass induce a greater decrease in immunologic response than CABG without cardiopulmonary bypass (off pump) operations. Nevertheless, off pump CABG operations do not induce a greater decrease in immunologic response than other surgical operations. © 2002, SAGE Publications. All rights reserved.
Keywords: cardiopulmonary bypass; cellular immunity; lymphocyte subsets; off pump